Utilisation of Digital Storytelling to Increase Student Learning Motivation - Solissa, Everhard Markiano; Yonaevy, Umy; Anggraheni, Dini; Febianti, Kurnia; Taqiyuddin, Taqiyuddin (World Psychology, 2024)
Digital storytelling is a form of mediated communication that uses a set of information and communication technologies with the aim of exchanging information, which is packaged into several topics with an interesting presentation style. The purpose of this study is to describe the utilization of digital storytelling that can increase the level of learning motivation of students. The research model implemented is to use quantitative methods. The quantitative method was carried out with a survey model with google forms and in-depth interviews, as well as gathering information from several students at one of the Madrasah Aliyah in the Tanah Datar area. The result of this research is that digital storytelling is very effective to be applied in schools, because it is able to bring out the enthusiasm and high motivation of students in learning. The conclusion of this research is that a teacher must be able to improvise on learning media which initially only used printed media in learning, now must be able to utilize digital storytelling as a medium that arouses students' enthusiasm. The limitation of this study is that researchers are only able to apply digital storytelling learning media in one subject. For this reason, researchers hope that future researchers can apply and develop digital storytelling in various subjects.